Analisis Laporan Keuangan Untuk Menilai Kinerja Keuangan Di PT Sucofindo Medan Periode 2019-2020 - Rizqia Amanda; Rahmat Daim Harahap (Institut Teknologi dan Bisnis (ITB) Semarang, 2024)
To measure the company's ability to generate profits, it can be seen from profitability ratio or profitability of the enterprise. The profitability of the company is measured by the success of the company and the ability to use its assets productively, namely by comparing the profit in a period with the total assets or amount of capital enterprises, where a high level of labor turnover can increase its profits. This study aims to analyze the internal control applied in the system cash management at PT Sucofindo.